Quality of life related to clinical aspects in people with chronic wound - Maicon Henrique Lentsck; Tatiane Baratieri; Maria Regiane Trincaus; Aline Padilha Mattei; Carine Teles Sangaleti Miyahara (SciELO, 2018)
ABSTRACT Objective: To evaluate the quality of life of people with chronic wounds and to compare this index with clinical parameters. Method: A cross-sectional study conducted between July 2014 and February 2015, evaluating people with chronic wounds in outpatient care during a nursing consultation, in the city of Guarapuava, Paraná. Quality of life was assessed by the Quality of Life Index - wounds version. Data were analyzed using the Mann Whitney test and T-test. Results: 53 people participated. The mean quality of life score was 22.65±3.08. The most significant scores in the analyzes were the family domain (27.71±2.94) with the highest mean score, and the health domain (18.91±4.58) had the lowest. Pain in walking (p=0.031) and using pain medication (p=0.002) presented a significant relation with overall score. There was a significant difference between the groups for the items pain at rest (p=0.022), pain in moving (p=0.006), using pain medication (p<0.001) and presence of infection (p=0.004), in the rest item (p=0.015) in the socioeconomic domain, and type of wound (p=0.05) and rest (p=0.041) in the psychological domain. Conclusion: The overall Quality of Life Index and by domains was classified as good and very good, where the family domain was better evaluated to the deriment of the health domain due to the clinical parameter of pain.